2000
DOI: 10.21273/hortsci.35.3.476e
|View full text |Cite
|
Sign up to set email alerts
|

479 Fruit Characteristics and Productivity of Date Palm Trees (Phoenix dactylifera L.) as Affected by Some Growth Regulators

Abstract: Date palm trees are among the most plentiful fruit trees in the Arabian Gulf States. Bioregulators have been used for the improvement of quality and productivity of date plam tree fruits. Application of gibberellic acid (GA3), naphthalene acetic acid (NAA), and ethephon, separately or in a mixture, has significant effects on fruit set, fruit dry matter percentage, fruit soluble percentage, fruit ripening, and yield of date palm trees. A study was conducted to assess relative effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…It also retarded fruit green color break of Sokary dates. This increment in fruit physical characteristics was also reported by numerous researchers working on different fruit species (Aljuburi et al, 2000;Stern et al, 2006;Aboutalebi and Beharoznam, 2006;Kassem et al, 2011). The improvement in fruit physical properties as a result of the different sprayed growth regulators might be due to their influence in enlarging cell size and enhancing the strength of carbohydrate sink, thus increasing fruit size and weight.…”
Section: Fruit Physical Characteristicssupporting
confidence: 80%
See 1 more Smart Citation
“…It also retarded fruit green color break of Sokary dates. This increment in fruit physical characteristics was also reported by numerous researchers working on different fruit species (Aljuburi et al, 2000;Stern et al, 2006;Aboutalebi and Beharoznam, 2006;Kassem et al, 2011). The improvement in fruit physical properties as a result of the different sprayed growth regulators might be due to their influence in enlarging cell size and enhancing the strength of carbohydrate sink, thus increasing fruit size and weight.…”
Section: Fruit Physical Characteristicssupporting
confidence: 80%
“…The increase in fruit total chlorophyll, TSS and total, reducing and non-reducing sugars at rutab or tamar stage and the decrease in acidity at rutab stage, as well as the decrease in fruit carotene content at rutab stage and in fruit acidity at tamar stage obtained in this present study by NAA, GA 3 and CPPU applications might translate their influence in retarding fruit ripening process as mentioned before Aljuburi et al, 2000) working on date palm. Sucrose synthase and invertase may be important in determining sink activity and could play critical roles in both phloem transport and in photosynthetic partitioning in sucrose-translocating plants (Ramezani and Shekafandeh, 2009).…”
Section: Fruit Chemical Characteristicssupporting
confidence: 76%
“…However, effect of PGRs on yield and plant development varied from species to species (Rademacher, 2015). A number of PGRs can be powerful tools for improving the growth and yield of oilseed crops as they can in some way modify plant development (Abdelgadir et al, 2010;Aljuburi et al, 2000;Ghosh et al, 1991). It was also reported that although PGR treatments altered the seed demand for resources in sesame, they failed to improve productivity (Day, 2000).…”
mentioning
confidence: 99%
“…The increasing of fruit chlorophyll using CPUU and NAA application comparing to control treatment (without growth regulators) may be due to their influence in delayed fruit ripening process as mentioned before (Moustafa and Seif, 1996; Aljuburi et al, 2000) working on date palm. The results is in harmony with (Kassem et al, 2012) who studied spraying Sokary date palm growing in Riyadh area, Saudi Arabia by NAA, GA3, CPPU, Put and SA substances increased significantly chlorophyll with all treatments (except Eth) during both seasons.…”
Section: Chlorophyll Contentmentioning
confidence: 74%
“…The increase in fruit total chlorophyllcontent obtained using NAA, GA3 and CPPU application might be due to their influence in retarding fruit ripening process as mentioned before by (Hussein et al 1996;Aljuburi et al 2000) working on date palm fruit. (h) Carotene.…”
Section: Vitamin Cmentioning
confidence: 74%